A Proposal for Environmental Awareness on the Path of Native Flora in Colliguaycito - Jaime Muñoz, Eduardo Antonio (2023)
The studio deals with the environmental path of native plants of Colliguaycito is located in the commune of Monte Patria, province of Limari, Region of Coquimbo, Chile. On this path, environmental education activities are carried out related to valuing the autochthonous plants that grow in this rural sector. However, there is a lack of environmental awareness of people who visit the environmental path. In this context, a proposal of environmental awareness arises, intending to develop educational activities with the aim of caring for and protecting the environmental path.Methodologically, a) a map was made of the area where environmental education activities are carried out, b) a cartography of the path was presented indicating the beginning and end of the path and the same cartography indicated the stops or viewpoints c) five exits were developed on the ground with the aim of identifying the environmental problems in the surroundings of the path, d) photographs are taken of some native plants and e) some actions are proposed to raise awareness of the people who visit the path. The results of this proposal contemplate the development of educational activities with the boys and girls who visit the path, such as learning the name, natural characteristics and uses of the plants that make up the path. Activities are also planned for the adult people who go there, such as recognition of native and endemic plants, developing actions in which people can participate and motivate the rest of the visitors on the importance of taking care of this natural space.